Distribution and inhibition of iron-oxidizing bacteria in relation to acid drainage from gold and coal mine dumps in the southern Transvaal - Bosch, Craig (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 1990.